Enhancing mouthguard longevity: Impact of surface treatment against aging from brushing and disinfectant exposure - Haddad e Borro, Larissa [UNESP]; de Queiroz, Talita Suelen [UNESP]; da Cruz, Beatriz Serralheiro [UNESP]; Demachkia, Amir Mohidin [UNESP]; Borges, Alexandre Luiz Souto [UNESP]; Tribst, João Paulo Mendes; Paes Junior, Tarcisio Jose de Arruda [UNESP] (Wiley, 2024)
Background/Aims: The study aimed to assess the surface characteristics of sports mouthguards under mechanical stresses during cleaning, either by brushing or immersion in disinfectant solutions. Material and Methods: Ethylene-vinyl acetate samples, 4 mm thick, were randomly assigned to cleaning methods: control (C—no cleaning), brushing with water (B.W), brushing with neutral liquid soap (B.S), brushing with toothpaste (B.T), immersion in distilled water for 10 min (I.W), immersion in 2.25% sodium hypochlorite solution for 10 min (I.SH), and immersion in sodium bicarbonate solution for 5 min (I.SB). All cleaning methods were applied for 28 days. Surface roughness average (Ra) and wettability were measured at baseline for the control group (n = 9), and after cleaning for all the other groups. Results: One-way ANOVA with Tukey tests (5% significance) indicated significant differences among groups (p <.05). The I.SB group had higher surface roughness than B.S and B.T (p <.05). B.W showed the lowest wettability, significantly lower than B.T, I.W, and I.SB (p <.05). I.SB exhibited the highest wettability, significantly different from sodium hypochlorite, neutral liquid soap, brushing with water, and control groups (p <.05). The sodium bicarbonate immersion group (I.SB) demonstrated greater statistical variation, displaying higher susceptibility to aging compared to brushing with neutral liquid soap. Conclusion: Cleaning mouthguards with a toothbrush, water, and neutral liquid soap emerged as the most promising method, causing minimal surface changes in the material.
Keywords: aging; cleaning; ethylene vinyl acetate; mouthguards